Ozone Evolution in the Past and Future - Rozanov, Eugene (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The stratospheric ozone is important for the protection of the biosphere from the dangerous ultraviolet radiation of the sun, forms the temperature and dynamical structure of the stratosphere, and, therefore, has a direct influence on the general circulation and the surface climate. The tropospheric ozone can damage the biosphere, impact human health, and plays a role as a powerful greenhouse gas. That is why the understanding of the past and future evolution of the ozone in different atmospheric layers, as well as its influence on surface UV radiation doses, and human health is important. The problems of preventing further destruction of the ozone layer, the restoration of the ozone shield in the future, and air quality remain important for society. The interest in these problems was recently enhanced by the unexpected discovery of a negative ozone trend in the lower stratosphere and the appearance of a large ozone hole over the Arctic in spring 2020. This book includes papers describing several aspects of the ozone layer's state and evolution based on the recent experimental, statistical, and modeling works. The book will be useful for readers, scientists, and students interested in environmental science.